2013
DOI: 10.1002/icd.1804
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Emotional Distress, Abuse Risk, and Children's Symptoms: Child Gender as a Moderator of Parent Sensitivity as a Mediator

Abstract: Mothers' distress is a correlate of their children's elevated behaviour problems and symptoms. Parenting practices have been shown to mediate these associations, but few studies have observed parenting or focused on parents at risk of child abuse. In this study of 269 high‐risk mothers and their young children (M = 4.2 years), structural equation modelling was used to test associations between mothers' distress and child externalizing and internalizing symptoms. Associations were expected to be partly indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Individual studies on parental sensitivity report considerable variability regarding the significance of associations with internalizing and externalizing problems. For example, studies have found parental sensitivity is not significantly associated with internalizing or externalizing problems (e.g., Benton et al, 2019), is significantly associated with externalizing but not internalizing problems (e.g., Easterbrooks et al, 2012), is significantly associated with internalizing but not externalizing problems (e.g., Zimmer‐Gembeck et al, 2013), or is significantly related to both (e.g., Sturge‐Apple et al, 2010). A number of meta‐analyses have also examined child behavior problems in relation to broader constructs of positive parenting, identifying significant associations between parental warmth or synchrony and children's reduced risk for externalizing problems ( r = −.18 to −.25; Pinquart, 2017a; Rothbaum & Weisz, 1994), internalizing problems ( k = 1015; r = −.20; Pinquart, 2017b), depression ( r = −24 to −.28; McLeod, Weisz, et al, 2007; Pinquart, 2017b), and anxiety ( r = −.06 to −.13; McLeod, Wood, et al, 2007; Pinquart, 2017b).…”
Section: Parental Sensitivity: Theory and Measurementmentioning
confidence: 99%
“…Individual studies on parental sensitivity report considerable variability regarding the significance of associations with internalizing and externalizing problems. For example, studies have found parental sensitivity is not significantly associated with internalizing or externalizing problems (e.g., Benton et al, 2019), is significantly associated with externalizing but not internalizing problems (e.g., Easterbrooks et al, 2012), is significantly associated with internalizing but not externalizing problems (e.g., Zimmer‐Gembeck et al, 2013), or is significantly related to both (e.g., Sturge‐Apple et al, 2010). A number of meta‐analyses have also examined child behavior problems in relation to broader constructs of positive parenting, identifying significant associations between parental warmth or synchrony and children's reduced risk for externalizing problems ( r = −.18 to −.25; Pinquart, 2017a; Rothbaum & Weisz, 1994), internalizing problems ( k = 1015; r = −.20; Pinquart, 2017b), depression ( r = −24 to −.28; McLeod, Weisz, et al, 2007; Pinquart, 2017b), and anxiety ( r = −.06 to −.13; McLeod, Wood, et al, 2007; Pinquart, 2017b).…”
Section: Parental Sensitivity: Theory and Measurementmentioning
confidence: 99%
“…Caregiver sensitivity appears to be important to the development of secure attachment (Ainsworth et al, 1974;Bakermans-Kranenburg et al, 2003), emotional and physiological regulation (Halligan et al, 2013;Nachmias et al, 1996;Rodrigues et al, 2021;Tarullo & Gunnar, 2006), and attentional capacities (Belsky, Pasco Fearon, et al, 2007), all of which are essential components of optimal socioemotional, behavioral, and cognitive functioning. However, there are substantial individual differences in parental sensitivity, and an array of risk factors that may impinge upon caregiver sensitivity, including familial psychosocial risk (e.g., Browne et al, 2018;Halligan et al, 2013;Prime et al, 2015;Sturge-Apple, Jones, et al, 2017), maternal experiences of ELA (Rahma et al, 2021), and maternal maladjustment and psychopathology (e.g., Coe et al, 2021;Pereira et al, 2012; Figure 1 The "3S Model of Family-Based Resilience" Vakrat et al, 2018;Zimmer-Gembeck et al, 2013). It is also important to highlight that many of these parental risk factors have been shown to increase the likelihood of intergenerational transmission of risk and maltreatment (van IJzendoorn et al, 2020).…”
Section: Sensitivitymentioning
confidence: 99%
“…Current research indicates parents with greater risk to abuse are more likely to perceive problematic behaviors in their children, an effect that has been observed in both community samples of parents [ 13 , 14 , 20 , 21 ] as well as clinical samples of at-risk children [ 22 , 23 ]. Longitudinal work suggests that parents reporting elevated stress are more likely to later report greater child behavior problems [ 13 , 24 ].…”
Section: Introductionmentioning
confidence: 99%